2020
DOI: 10.1177/1071100720920274
|View full text |Cite
|
Sign up to set email alerts
|

Multiplanar Semiautomatic Assessment of Foot and Ankle Offset in Adult Acquired Flatfoot Deformity

Abstract: Background: Semiautomatic 3-dimensional (3D) biometric weightbearing computed tomography (WBCT) tools have been shown to adequately demonstrate the relationship between the center of the ankle joint and the tripod of the foot. The measurement of the foot and ankle offset (FAO) represents an optimized biomechanical assessment of foot alignment. The objective of this study was to evaluate the correlation between FAO and traditional adult acquired flatfoot deformity (AAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Traditional and novel measurements in 3D can be used for thorough assessments before and after operation 61 . In addition to the effective Foot–Ankle-Offset 62 , 63 , other new indexes representing the overall foot deformities in a single value shall be defined, to support better the clinical decision making process. Also the current multi-planar measures of articular subluxations 19 can be ameliorated with complete 3D bone models.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional and novel measurements in 3D can be used for thorough assessments before and after operation 61 . In addition to the effective Foot–Ankle-Offset 62 , 63 , other new indexes representing the overall foot deformities in a single value shall be defined, to support better the clinical decision making process. Also the current multi-planar measures of articular subluxations 19 can be ameliorated with complete 3D bone models.…”
Section: Discussionmentioning
confidence: 99%
“…WBCT has recently become an important diagnostic imaging tool to evaluate not only the severity of PCFD 10,11,[14][15][16]18,19 but also the widening and instability of DTFS injuries. 7,28,[33][34][35]43,49 The FAO was proposed by Lintz et al 38 as a 3D semiautomatic tool for a multiplanar assessment of foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…The FAO has been shown to be a very reliable measurement 12,17,39,54 and was recently validated to be used in the specific assessment of patients with PCFD. 10,11 It has been demonstrated by de Cesar Netto et al 11 that FAO represents in a single measurement multiple components of the multiplanar PCFD assessment, assessing longitudinal arch collapse (forefoot arch angle), PTS (subtalar horizontal angle), hindfoot valgus alignment (hindfoot moment arm), and forefoot/midfoot abduction (talonavicular coverage angle). Day et al 10 have also recently demonstrated that FAO measures also accurately demonstrate the amount of overall surgical correction following reconstructive surgical procedures in PCFD, with values of FAO decreasing from 9.8% preoperatively to a mean postoperative value of 1.3% (P < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, WBCT provides more clinically useful information concerning alignment as it is performed under natural standing conditions. 2,[17][18][19][20]22,23,28,33,34,47 Multiple parameters have been previously used to assess the hindfoot alignment on WBCT, including the foot ankle offset, 5,6,17,19,23,29,[33][34][35]47 calcaneal offset, 5,6,19,29,35 and hindfoot alignment angle. 5,6,10,30 Although WBCT offers the theoretical benefits of increased accuracy present in crosssectional imaging coupled with physiologic alignment under weightbearing conditions, this technology is currently less prevalent in orthopedic clinics across the community where HAV radiographs are generally utilized.…”
Section: Introductionmentioning
confidence: 99%